Avaliação da correlação entre capacidade antioxidante e escurecimento enzimático de novos cultivares de maçãs - Ercoli, Luciana (2013)
The apple (Malus domestica Borkh) consumed in very different regions of the world is a rich fruit in phenolic compounds, which vary according to the cultivar and part of the fruit analyzed. This study aimed to analyze genetically improved varieties of apples performing correlation study between enzymatic browning and antioxidant capacity. Some genetically improved cultivars in this study had a delay in enzymatic browning. The sample is composed of seven genetically improved cultivars of apples and three commercial (Epagri-170/25, Epagri-170/40, Epagri-170/65, Epagri-170/91, Epagri-M11/00, Epagri-M3/02, Epagri-M15/07, Daiane, Monalisa and Jazz. The samples were evaluated for the analytical results and the correlations between antioxidant capacity (applying the DPPH and FRAP assays), polyphenol concentration (FT), anthocyanins, ascórbido acid, darkening Enzyme (% E), PPO activity (APPO) and total acidity (TA). Higher levels of phenolics present in apples skins and pulps were obtained by cultivating Epagri-170/91. Analysis of antioxidant capacity of the shells showed that the best results were found for the Epagri-170/91and Epagri-170/25 applying the DPPH test and FRAP, respectively. Analyzes of the pulps show that the best results were observed in cultivating Epagri-M3/02 (DPPH assay) and Epagri-170/91 (FRAP assay). The antioxidant capacity values were correlated with the contents of total phenolics and the results showed values of R> 0.7, indicating that the polyphenolic compounds contribute to antioxidant activity of the fruits. Among the Epagri samples, some showed a delay in some enzymatic browning when exposed to oxygen in the air for a long period of time. Thus, analysis of the activity and enzymatic browning carried out showed that the most significant responses were for Epagri-170/91 and Epagri-170/25. Pearson correlation analysis for the evaluation was conducted and the highest values were observed for correlations ATT x % E (R = 0,773), APPO x% E (R = 0,658) indicating that the browning of the fruits is inversely proportional to the acidity and PPO activity.